2018
DOI: 10.1002/jbt.22168
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR‐874‐3p and miR‐874‐5p inhibits epithelial ovarian cancer malignancy via SIK2

Abstract: Based on miR-874 expression levels in the GSE47841 microarray, we hypothesized that the mature products of miR-874, miR-874-3p, or miR-874-5p, would inhibit epithelial ovarian cancer (EOC) cell proliferation, metastasis, and chemoresistance. We first examined miR-874-3p and miR-874-5p expression levels in primary EOC tumor tissue samples and found that they were significantly decreased. 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) cell proliferation and transwell assays revealed that miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 36 publications
(42 reference statements)
1
35
0
Order By: Relevance
“…Our research found that when the SIK2 expression in BC cells was silenced, their proliferation, invasion and aerobic glycolysis ability enhanced significantly, while the opposite phenomenon was observed after the SIK2 expression increased further. Previous studies [21] have found that inhibiting the expression of SIK2 can inhibit the growth of ovarian cancer cells, suggesting that SIK2 was effective as a oncogene, which is similar to our conclusion. Subsequently, to investigate the effect of SIK2 on DDP resistance of BC cells, we established a cisplatin-resistant cell line and analyzed the sensitivity of SIK2 to DDP in cells after intervention.…”
Section: Discussionsupporting
confidence: 92%
“…Our research found that when the SIK2 expression in BC cells was silenced, their proliferation, invasion and aerobic glycolysis ability enhanced significantly, while the opposite phenomenon was observed after the SIK2 expression increased further. Previous studies [21] have found that inhibiting the expression of SIK2 can inhibit the growth of ovarian cancer cells, suggesting that SIK2 was effective as a oncogene, which is similar to our conclusion. Subsequently, to investigate the effect of SIK2 on DDP resistance of BC cells, we established a cisplatin-resistant cell line and analyzed the sensitivity of SIK2 to DDP in cells after intervention.…”
Section: Discussionsupporting
confidence: 92%
“…Identification of ERN1 is noteworthy given that during the ER stress response, this gene encodes the ER stress sensor inositol-requiring enzyme 1 (IRE1a), responsible for the unconventional cleavage of a 26 nucleotide fragment from Xbp1 mRNA, resulting in the generation of the active spliced variant of XBP1 (XBP1s) and enabling it to function as a potent transcription factor (17). Additional candidate drivers in fetal bone marrow following maternal OM-85 treatment included CD38, IL5 and an array of microRNAs (miR) ( Figure 3A right panel; Supplemental Table 5) recognised principally in the context of cancer-associated functions (18)(19)(20). It is important to note however, that miR-149-3p has been shown to negatively regulate Toll-like receptor (TLR) 4 expression in murine monocytic cells in vitro (21) and it is possible that other miRs may have similar (but as yet undefined) innate immune regulatory functions (22).…”
Section: Resultsmentioning
confidence: 99%
“…An increasing number of studies confirm that miRNAs participate in various tumors, such as with respect to tumor migration and proliferation. miR‐874‐3p expression is abnormally decreased in various cancers, including ovarian cancer, 19 colorectal cancer 20 and hepatocellular carcinoma 21 . Zhu et al 12 .…”
Section: Discussionmentioning
confidence: 99%